Managing diversity with new technology – origin or solution of digital divide?. - Bolz, Hannah; Bonitz, Melanie (Pupils’ Diversity and Integration in Education – German and Malaysian Perspectives, 2016)
Managing diversity in schools means handling educational disadvantages based on disadvantages in movement disorders, different intellectual and verbal skills, economical differences and although social, emotional and motivational aspects and giving everyone the best possible prospect to develop their own skills. Promote equal opportunities to children of different backgrounds should be one key function of school system next to socialization, allocation, selection and of course qualification (vgl. Fend 2006: 49–54). Following the question if it is possible to compensate drawbacks originating from students’ diversity with digital technology or if digitalization lead to an even deeper Digital Divide. The text follows the assumption that digital technology produces more inequality in educational contexts and at the same time supports equal opportunities in educational contexts. The fact that the digital technology is a part of our everyday life, forms the basis of these both acceptances. After a theoretical basis and an overview to some research findings in context of the central question the article will give some practical examples how teachers at German schools use digital media to meet the individual students’ needs and which concepts stand behind their approach.
Keywords: Digital Literacy; Digital Divide; Diversity; Media Education